Size Matters: From Two‐Dimensional AuI–TlI Metallopolymers to Molecular Complexes by Simple Variation of the Steric Demand. Issue 15 (18th February 2019) - Seifert, Tim P.; Knoefel, Nicolai D.; Feuerstein, Thomas J.; Reiter, Kevin; Lebedkin, Sergei; Gamer, Michael T.; Boukis, Andreas C.; Weigend, Florian; Kappes, Manfred M.; Roesky, Peter W.
Abstract: Bis(acetylido) aurates(I) and thallium(I) trifluoromethylsulfonates were used to synthesize Au I –Tl I metallopolymers, displaying novel and unusual structural motifs of the metal–metal backbones in the solid state: a discrete molecular cluster, 1D chains of interconnected dimers, tetramers, or dodecamers of Au–Tl units, and a 2D‐plane network, consisting of alternating edge‐linked (AuTl)6 and (AuTl)4 cycles. The formation of the different architectures was primarily controlled by the steric demand of the acetylide‐substituent groups. Thus, the bulkiest 2, 6‐diisopropylphenyl derivative yielded a molecular cluster [Tl2 Au3 ]. Most compounds showed bright visible photoluminescence with quantum yields of up to 25 % at ambient temperature. The color of the emitted light significantly differs with the network structure. Furthermore, theoretical studies of singlet excitations in the molecular cluster, as well as NMR and mass‐spectrometric investigations of the fragmentation of the metallopolymers in solution are described in detail. Abstract : Bigger for better or worse : Luminescent Au I –Tl I metallopolymers, displaying novel and unusual structural motifs of the metal–metal backbones in the solid state, are reported.